2020
DOI: 10.32479/ijeep.10605
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of External Debt on Emissions: Evidence From China

Abstract: In this study, the effect of external debt (EXD -current US$) on carbon dioxide emissions (CO 2 -metric tons per capita) is examined by taking the environmental Kuznets curve (EKC) hypothesis as a basis for China. The relationships between CO 2 , gross domestic product per capita (GDP -constant 2010 US$), square of GDP (GD), energy consumption (EM -kg of oil equivalent per capita) and EXD is examined. The autoregressive distributed lag (ARDL) model and nonlinear ARDL model are used to examine symmetric and asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The findings showed that there is important linkage among CO 2 emissions, energy, real income and external debt in Turkey. [ 39 ] employed the ARDL technique to explore the effect of public debt on the level of CO2 emissions in China over the tested period from 1978 to 2014. The findings showed a positive and significant influence of external debt on the level of environmental pollution in China.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The findings showed that there is important linkage among CO 2 emissions, energy, real income and external debt in Turkey. [ 39 ] employed the ARDL technique to explore the effect of public debt on the level of CO2 emissions in China over the tested period from 1978 to 2014. The findings showed a positive and significant influence of external debt on the level of environmental pollution in China.…”
Section: Review Of Literaturementioning
confidence: 99%
“…By using a vector error correction model, Katircioglu and Celebi (2018) do not find any evidence for the effect of ED on CO2 emissions in Turkey during the 1960-2013 period. In the case of China, Beşe et al (2021b) use ARDL and nonlinear ARDL models and find a significant positive effect of ED on CO2 emissions for the 1978-2014 period. By using the same methodologies, Beşe et al (2021a) analyze the effect of external debt on different types of emissions in India between 1971 and 2012.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, the (CREDIT) effects on the human development are also analyzed by many empirical studies, such as that of [74,99,[107][108][109] among others, and included the external debt variable in their empirical models to examine their impacts on economic growth. In addition, as for ( [110], they used this variable in their model to study its effect on the carbon dioxide emissions (CO 2 ) in the case of China, whereas [111] included the external debt variable in his empirical study in order to analyze its impact on human development.…”
Section: Presentation Of the Modelmentioning
confidence: 99%